2015
DOI: 10.1149/2.0601507jes
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrochromic Properties of Vanadium Pentoxide Nanorods Prepared by Thermal Treatment of Sol-Gel Dip-Coated Thin Films

Abstract: Porosity in the sol-gel prepared vanadium pentoxide film is created by using templating methods. The morphology, optical and electrochromic properties of the macro-and mesoporous films, prepared in the presence of structure-directing agents such as polystyrene microspheres and triblock copolymer, have been compared with those of dense films. By using various methods to remove the template material, it was shown that the morphology of the vanadium pentoxide film can be controlled and new nanostructures can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The Raman scattering spectra for a dip‐coated V 2 O 5 thin film on ITO substrates deposited by Alsawafta et al is shown in Figure b, where the precursor solution was prepared from a mixture of vanadium oxytriisopropoxide, IPA and acetic acid . The Raman scattering spectra in Figure b shows the thin films in an as‐deposited state prior to annealing where no distinct Raman modes indicative of orthorhombic V 2 O 5 are noted, but are subsequently observed after crystallization at 500 °C …”
Section: Comparison Of Thin Film Deposition For Vanadium Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Raman scattering spectra for a dip‐coated V 2 O 5 thin film on ITO substrates deposited by Alsawafta et al is shown in Figure b, where the precursor solution was prepared from a mixture of vanadium oxytriisopropoxide, IPA and acetic acid . The Raman scattering spectra in Figure b shows the thin films in an as‐deposited state prior to annealing where no distinct Raman modes indicative of orthorhombic V 2 O 5 are noted, but are subsequently observed after crystallization at 500 °C …”
Section: Comparison Of Thin Film Deposition For Vanadium Oxidesmentioning
confidence: 99%
“…While the precursor that comprises two solutions may be the same, the mixture ratio of the individual components, alkoxide/solvent for example, is often altered for the specific purpose of the experiment. Chen et al prepared a vanadium pentoxide (V 2 O 5 ) alkoxide precursor solution for forming thin films with an IPA‐Alkoxide‐H 2 O mixture ratio of 76‐1‐19, whereas the same precursor solution is also used by others at different IPA‐Alkoxide ratios of 9‐1, 25‐1 and 100–1 . In each case, a V 2 O 5 thin film was formed from an alkoxide precursor solution where a best‐fit ratio can be chosen in order to attain desired deposit morphologies.…”
Section: Precursor Solutions: Design and Preparation For Solution‐basmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that template sol-gel prepared vanadium oxide films yield, after removing the template, meso-(pores in the size range of 2 to 20 nm) or macroporous films with significantly enhanced electrochromic properties [23][24][25][26][27][28][29][30][31][32]. The morphology and optical and electrochromic properties of the macro-and mesoporous films, prepared in the presence of structure-directing agents, have been compared with those of dense films [23]. The transformation of the lamellar into a nanorod structure, observed when the film is heated at 400-500 ∘ C for several hours, resulted in the development of an elegant method for the synthesis of vanadium oxide nanorods [23].…”
Section: Introductionmentioning
confidence: 99%
“…One of the more commonly utilized sol-gel methods is based on the reaction of the metallic tungsten with hydrogen peroxide that results in the formation of stable solutions of peroxopolytungstic acid, which contains the ðW 2 O 11 Þ 2− anion. [20][21][22][23] By using a dip-coating deposition technique and suitable annealing temperatures, our group and others have prepared nanostructured thin films of tungsten oxide and its golddoped composites that have very good EC properties.…”
mentioning
confidence: 99%